Unraveling concordant and varying responses of oyster species to Ostreid Herpesvirus 1 variants - Friedman, Carolyn S.; Reece, Kimberly S.; Wippel, Bryanda J.t.; Agnew, M. Victoria; Dégremont, Lionel; Dhar, Arun K.; Kirkland, Peter; Macintyre, Alanna; Morga, Benjamin; Robison, Clara; Burge, Colleen A. (Science of The Total Environment, 2020)
The Ostreid herpesvirus 1 (OsHV-1) and variants, particularly the microvariants (μVars), are virulent and economically devastating viruses impacting oysters. Since 2008 OsHV-1 μVars have emerged rapidly having particularly damaging effects on aquaculture industries in Europe, Australia and New Zealand. We conducted field trials in Tomales Bay (TB), California where a non-μVar strain of OsHV-1 is established and demonstrated differential mortality of naturally exposed seed of three stocks of Pacific oyster, Crassostrea gigas, and one stock of Kumamoto oyster, C. sikamea. Oysters exposed in the field experienced differential mortality that ranged from 64 to 99% in Pacific oysters (Tasmania>Midori = Willapa stocks), which was much higher than that of Kumamoto oysters (25%). Injection trials were done using French (FRA) and Australian (AUS) μVars with the same oyster stocks as planted in the field and, in addition, two stocks of the Eastern oyster, C. virginica. No mortality was observed in control oysters. One C. virginica stock suffered ~10% mortality when challenged with both μVars tested. Two Pacific oyster stocks suffered 75–90% mortality, while one C. gigas stock had relatively low mortality when challenged with the AUS μVar (~22%) and higher mortality when challenged with the French μVar (~72%). Conversely, C. sikamea suffered lower mortality when challenged with the French μVar (~22%) and higher mortality with the AUS μVar (~44%). All dead oysters had higher viral loads (~1000×) as measured by quantitative PCR relative to those that survived. However, some survivors had high levels of virus, including those from species with lower mortality. Field mortality in TB correlated with laboratory mortality of the FRA μVar (69% correlation) but not with that of the AUS μVar, which also lacked correlation with the FRA μVar. The variation in response to OsHV-1 variant challenges by oyster species and stocks demonstrates the need for empirical assessment of multiple OsHV-1 variants.